Effects of thermal aging and ionizing radiation on sPVC and aromatic polyether urethane used to store nuclear materials. (September 2019) - Dumont, Joseph H.; Murphy, Eamonn; Geller, Drew; Lee, Kwan-Soo; Labouriau, Andrea
Abstract: The present work tested the degradation of two polymeric materials under conditions routinely encountered in nuclear applications. Polymers in the form of plastic bags are commonly used along with metal containers to store and transport nuclear materials. The role of the bag, also known as bag-out bag, is to prevent contamination in case the metal containers are breached. Polymeric materials of interest are sPVC and aromatic polyether urethane (APU-ether), which in this study were exposed to alpha, gamma and thermal conditions. These conditions were specifically chosen to simulate the harsh environments normally encountered in the storage of nuclear materials. The physical, chemical and mechanical properties of these materials were investigated by a series of characterization methods before and after exposures. Our results highlight the superior stability of APU-ether under thermal aging and ionizing radiation and provide new insights into the durability of polymeric materials used in nuclear applications. These findings will serve as the foundation for a rational selection of new bag-out bag materials to be considered in the nuclear industry. Highlights: Polymeric materials have been subjected to accelerated aging. Conditions include temperature, gamma and alpha radiation. Materials were tested before and after exposure. Plasticized polyvinylchloride properties change rapidly through dehydrochlorination. Aromatic polyether urethane shows no significant changes.